Percutaneous insertion of peritoneal dialysis catheters using ultrasound and fluoroscopic guidance: A single centre experience and review of literature. Issue 6 (15th June 2015) - De Boo, Diederick W; Mott, Nigel; Tregaskis, Peter; Quach, Trung; Menahem, Solomon; Walker, Rowan G; Koukounaras, Jim
Summary: Various methods of peritoneal dialysis (PD) catheter insertion are available. The purpose of this study was to evaluate a percutaneous insertion technique using ultrasound (US) and fluoroscopy performed under conscious sedation and as day case procedure. Data of 87 percutaneous inserted dialysis catheters were prospectively collected, including patients' age, gender, body mass index, history of previous abdominal surgery and cause of end stage renal failure. Length of hospital stay, early complications and time to first use were also recorded. Institutional review board approval was obtained. A 100% technical success rate was observed. Early complications included bleeding ( n  = 3), catheter dysfunction ( n  = 6), exit site infection ( n  = 1) and exit site leakage ( n  = 1). All cases of catheter dysfunction and one case of bleeding required surgical revision. Median time of follow‐up was 18 months (range 3–35), and median time from insertion to first use was days 14 (1–47). Of the 82 patients who started dialysis, 20 (23%) ceased PD at some stage during follow‐up. Most frequently encountered reasons include deteriorating patient cognitive or functional status ( n  = 5), successful transplant kidney ( n  = 4) and pleuro‐peritoneal fistula ( n  = 4). Sixty‐two (71%) PD catheter insertions were performed as day case. The remaining insertions were performed on patients already admitted to the hospital. Percutaneous insertion of dialysis catheter using US and fluoroscopy is not only safe but can be performed as day case procedure in most patients, even with a medical history of abdominal surgery and/or obesity.